Climate Smart Cocoa: a mobile application for climate smart cocoa cultivation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CSC implementer mobile Application has been developed and soon to be available on google app stores for free downloads.This App is currently being reviewed by our partners for feedback.